Antenatal teratoma sacrococcygeal in a three month old children in Indonesia: a rare case report - Ibrohim, Ibnu Sina; Suwardi; Haryono, Dedy C.; Irwansyah, Bambang (International Surgery Journal, 2024)
Sacrococcygeal teratoma is a type of germinal cell tumor in children, usually observed in the prenatal or antenatal phases. In either phase, sacrococcygeal teratoma may cause complications that lead to increased risk of morbidity and mortality. A proper screening and management for sacrococcygeal in children are mandatory for the best outcome. Currently, surgical resection is the most promising treatment to manage antenatal sacrococcygeal teratoma in children. Three-month-old female children were brought to the hospital with a growing 8.4 cm mass since birth in her groin. The mass was painless and soft in consistency. Computed tomography (CT) scan revealed a dominant solid lesion accompanied by multiloculated fluid density arising from right gluteal muscle. The patient planned for surgical excision. Hyperkalemia was observed prior to the operation; hence an appropriate correction was needed before surgery. Germ cell tumors, though uncommon, may develop beyond the gonadal region, such as in the brain, neck, mediastinum, and retroperitoneum. In neonates and fetuses, these tumors frequently originate in the sacrococcygeal area, possibly resulting from the migration of primordial cells and the proliferation of totipotent stem cells in that region. Optimal disease burden outcomes for sacrococcygeal teratoma are often achieved through surgical resection. Sacrococcygeal teratoma, although rare, might possess a mortal threat to patient, hence proper diagnosis and treatment must be done to ensure the best clinical outcome.